The Effectiveness of the Virtual Lab in Acquiring the Periodic Movement Concepts in Physics among Grade 11 Students in Sharqiya South Governorate-Sultanate of Oman - Al-Salti, Taher Jumaa; Kraishan, Osama Marzouq (Journal of Curriculum and Teaching Methodology, 2025)
This study aimed to reveal the effectiveness of the virtual lab in acquiring concepts of periodic movement among 11th grade students in physics. To achieve the aim of the study, the researcher used a quasi- experimental approach. The study was applied in two schools from the same environment, where the sample consisted of (59) students from the 11th grade students in Lababa Bint Al-Hareth School (10-12) and Al-Khansa school (10-12) in Sharqiya South Governorate. enrolled in 2019-2020 academic year. The sample divided into two groups, experimental (27) teached with Virtual Lab strategy, and control (32) teached with conventional method. The application of the research was for (22) Teaching session in the first semester. To achieve the goals and to answer the hypothesis of the study the researcher applied a teacher’s guide, which worked out to guide the teacher for teaching the experimental group by virtual laboratory. The charity was verified by presenting it to a group of arbitrators. As for the study tool, it consisted of an achievement test of the concepts of periodic motion in physics. Its reliability was calculated by the Alpha Cronbach.The results of the study indicated that there are statistically significant differences between the mean scores of achievement of the experimental group and the control group in the subsequent test in the general examination in favor of the experimental group.In the light of these findings the researcher concluded a number of recommendations, Inviting physics teachers to use different types of virtual programs like Crocodile, Edison and Circuit Shop when explaining the units in physics. The researcher also concluded and suggested to Holding training workshops for physics teachers.
Keywords: virtual laboratory; concepts of periodic motion; Physics